Awareness of Being at Risk of Stroke and Its Determinant Factors among Hypertensive Patients in Banyumas, Indonesia - Ismail Setyopranoto; Arif Setyo Upoyo; Atyanti Isworo; Yunita Sari; Amelia Nur Vidyanti (Stroke Research and Treatment)
Background. The global burden of stroke is still high, particularly in developing countries, with hypertension serving as the main risk factor. The awareness of stroke among hypertensive patients is crucial for stroke prevention. This study was aimed at identifying the awareness of being at risk of stroke and its determinant factors among hypertensive patients in Banyumas, Indonesia. Methods. This was a cross-sectional study conducted in Primary Health Centers (PHCs) in Banyumas Regency, Indonesia, from April to August 2019. A simple random sampling technique was used to select the representatives’ PHCs. Hypertensive patients who came regularly to the PHCs were consecutively recruited. Data were collected through a self-reported questionnaire and medical records. The main outcome was the level of participants’ awareness of being at risk of stroke. Multivariate logistic regression analysis was performed to measure determinant factors associated with the level of awareness. Results. Out of 457 patients investigated, 77.46% had a low level of awareness. Low knowledge of hypertension, low income, and no history of previous stroke were associated with a low-level of awareness (odds ratio (OR) 1.942, 95% CI 1.195-3.158, p 0.007; OR 2.321, 95% CI 1.326-4.064, p 0.003; and OR 6.033, 95% CI 2.450-14.858, p<0.001, respectively). Conclusion. Majority of hypertensive patients were unaware of being at risk of stroke. Knowledge of hypertension, income, and history of previous stroke are factors that may influence the awareness of being at risk of stroke among them. This emphasizes the need to provide better campaigns and education programs to raise the awareness of stroke in a community setting, particularly for the population at risk.